Prediksi Financial Distress dengan Pendekatan Model Ohlson O-Score Pada Perusahaan Sektor Property dan Real Estate Periode 2022-2024 - Asnanil Khoiriyah; Era Yudistira; Esty Apridasari; Witantri Dwi Swandini (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the prediction of financial distress among 14 companies in the property and real estate sector listed on the Indonesia Stock Exchange for the period 2022–2024. Using a descriptive quantitative method, this study applies the Ohlson O-Score model, which integrates nine financial variables, including firm size, solvency, liquidity, and profitability. The threshold (cut-off) used is 0.38, where a score above this value indicates a state of distress. The results of the analysis indicate a significant risk of bankruptcy, with the number of companies experiencing distress increasing from 8 companies in 2022 to 11 companies in 2024. An in-depth anal-ysis identified that in 2022, the firm size factor (O1) was the primary determinant of financial resilience; however, conditions deterio-rated by 2023, with 9 firms experiencing distress due to structural failures resulting from an imbalance between operating cash flow and liability burdens (O7) as well as a drastic decline in profitability (O9). Peaking in 2024, financial risk reached a critical point where only 3 companies (DMAS, BEST, BSDE) were deemed healthy, while the other 11 were trapped in distress. Even large companies with positive nominal profits, such as PWON and SMRA, remained trapped in the distress zone due to low operational efficiency and debt burdens exceeding their cash flow capacity. This situation was exacerbated by post-pandemic external pressures, including a rise in the benchmark interest rate to 6% and high inflation, which increased the cost of borrowing, so that by the end of the observa-tion, the analysis indicated a significant increase in bankruptcy risk in the property and real estate sector during the observation peri-od, showing that 6 companies remained in distress throughout the observation period (APLN, ASRI, CTRA, LPKR, MTLA, and SMRA), while only DMAS and BSDE were able to maintain a non-distressed status. Overall, the Ohlson O-Score model proved effective as an early warning system for management and investors in identifying the vulnerability of the property and real estate sector to economic pressures.